FRI0262 The Role of 18F-FDG-PET/CT in the Diagnosis and Follow-Up of Large Vessel Vasculitis. (9th June 2015) - Pazzola, G.; Casali, M.; Muratore, F.; Pipitone, N.; Boiardi, L.; Aldigeri, R.; Versari, A.; Salvarani, C.
Abstract : Background: PET/CT has been proposed as a useful tool to diagnose and monitor activity in the large-vessel vasculitides (LVV) giant cell arteritis (GCA) and Takayasu's Arteritis (TAK), but the best approach to evaluate vascular uptake still remains debated. Both GCA and TAK often present with non-specific symptoms and laboratory test results. 18F-FDG PET/CT (PET/CT) has shown its potential to diagnose LVV earlier than any other traditional imaging techniques. Objectives: The aim of this study was to investigate the role of PET/CT in assessing disease activity in patients with LVV, and to compare different semi-quantitative vascular FDG grading approaches. Methods: 28 Patients with LVV underwent a total of 135 PET/CT scans and were compared to 29 matched controls. All PET/CT scans were reviewed by a nuclear physician blinded to clinical data. A semi-quantitative analysis using the maximum and mean standardized uptake value (SUVmax, SUVmean), was performed. Vascular to liver, to spleen, to blood pool, and to muscle ratios, were, respectly, determinated, to minimize the effects of time from injection to acquisition, and of blood glucose level. PET/CT findings were correlated to the clinical indices ITAS (Indian TAK activity score) and Kerr/National Institute of Health (Kerr/NIH), as well as to serum acute-phase reactants levels (erythrocyte sedimentation rate [ESR] and C-reactive protein [CRP]). Results: Arterial SUVmax was significantly higher in LVV (both active and inactive) patients than in controls in the following vascular districts: carotid (p 0.015-0.046), subclavian (p=0.035) arteries, thoracic (ascending, arch and descending) and abdominal aorta (p 0.0001-0.003). Arterial to liver SUVmax ratio (SUVmaxAorta-Liver ratio), arterial to spleen SUVmax ratio (SUVmaxArterial-Spleen ratio), and arterial to venous blood pool SUVmax ratio (SUVmaxArterial-Blood pool ratio) discriminated active from inactive LVV better than the arterial to muscular (gluteal) ratio (SUVmaxArterial-Muscle ratio). In particular SUVmaxAscending Aorta - Liver ratio with a cut off value of 0.65, provided a diagnostic sensitivity of 76% and a specificity of 79% (AUC =0.791). Using a cut-off value of 0.9 for the highest SUVmaxDescending Aorta - Liver ratio, it was possible to discriminate between active and inactive TAK patients with a sensitivity of 70% and a specificity of 92% (AUC =0.817). In GCA a cut-off value of 0.9 for SUVmaxAortic Arch-Spleen ratio, SUVmaxDescending Aorta-Spleen ratio, SUVmaxAortic Arch-Liver ratio, SUVmaxDescending Aorta–Liver ratio was able to discriminate active from inactive patients with a sensitivity of 70% and a specificity of 87% (AUC =0.84-0.87). Conclusions: PET/CT is a useful tool for diagnosis and follow-up of LVV. In particular, SUVmaxDescending Aorta-Liver ratio in Takayasu, and SUVmaxAorta-Liver ratio, SUVmaxAorta-Spleen ratio, and SUVmaxAorta-Blood Pool ratio in GCA appeared the most useful tools in monitoring the disease activity during the follow-up. Disclosure of Interest: None declared